Accumulation of Sulphate and Nitrate in IMLI ( Tamarindus indica L.) Tree Bark as Indicator of Atmospheric Pollution at Indore (M.P.) India - Trivedi, Priya (International Journal of Scientific Research in Biological Sciences, 2021)
Bio-monitoring of air quality in Indore city was investigated by analyzing the accumulation of sulphate and nitrate in the bark of Tamarindus indica L. by measuring their concentration using a double beam spectrophotometer. The samples were taken from different polluted areas (mixed (MPA), vehicular (VPA), industrial (IPA), and control sites (LPA)) in different seasons. The results of the present study show sulphate and nitrate accumulation more in the rainy season at all pollution areas while maximum sulphate accumulation was found at IPA i.e. 36.9 mg kg -1 whereas it was 27.3 mg kg -1 at MPA for nitrate in the rainy season. The minimum sulphate was 16 mg kg -1 at VPA in the summer season while it was 14.8 mg kg -1 for nitrate at MPA in the winter season. A maximum % increase for sulphate was found at IPA in the summer season i.e. 88.03 % while it was 67.48 % in the rainy season at MPA for nitrate respectively. The research also confirms the suitability of the Tamarindus indica tree as a suitable bio-indicator and will help to reduce the gaseous as well as particulate pollution in the city.